2014
DOI: 10.1177/2325957414555230
|View full text |Cite
|
Sign up to set email alerts
|

I Am Men’s Health

Abstract: In 2012, the US Food and Drug Administration approved Truvada as a pre-exposure prophylaxis (PrEP) for adults at risk of HIV. PrEP is highly effective at preventing HIV when taken daily, but no gold standard exists for consistently administering PrEP to populations at highest risk. The "I Am Men's Health" program used an innovative methodology to generate adherence to PrEP in 23 mostly young men who have sex with men of color (yMSMc), during a 28-week period from February to September 2013. Adherence was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 8 publications
(12 reference statements)
0
29
0
Order By: Relevance
“…The prospect of social ostracism and prosecution introduces further structural barriers to accessing healthcare services, reducing PrEP uptake and adherence. In a study of young MSM of colour in the USA, 39% had been kicked out of their home due to their sexual orientation and 43% had spent at least one night on the street [ 50 ]. These factors, combined with the prevalence of transactional sex, mean that young women and MSM, particularly transgender women, are often subject to abuse [ 5 , 50 ] and frequently lack decision-making power over their bodies when it comes to sexual encounters [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prospect of social ostracism and prosecution introduces further structural barriers to accessing healthcare services, reducing PrEP uptake and adherence. In a study of young MSM of colour in the USA, 39% had been kicked out of their home due to their sexual orientation and 43% had spent at least one night on the street [ 50 ]. These factors, combined with the prevalence of transactional sex, mean that young women and MSM, particularly transgender women, are often subject to abuse [ 5 , 50 ] and frequently lack decision-making power over their bodies when it comes to sexual encounters [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous PrEP demonstration projects and clinical trials that have included PrEP utilized a full clinical staff including clinicians, lab technicians, social workers, and counselors devoted to PrEP education, initiation, and retention [12, 13, 21–23]. Several projects offered regular clinical hours allowing for “drop in” visits and also provided additional support services including counseling, meal/housing assistance, and leadership/job training courses [12, 21]. Notably, a few studies were incentivized and recruited individuals already interested in taking PrEP [13, 21, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have relied on external referrals for PrEP outside of the research study context [9]. A referral-based program may not fully address these barriers for YBMSM as many lack access to healthcare [8, 1214]. Here, we describe the implementation of an optional PrEP program as an addition to a standard package of HIV prevention services in a currently enrolling, HIV/STI incidence cohort of YBMSM in Atlanta, GA. A detailed understanding of facilitators and barriers to PrEP uptake among YBMSM is necessary to inform the development of targeted interventions to promote PrEP uptake and adherence within this population.…”
Section: Introductionmentioning
confidence: 99%
“…We have also identified six intervention development studies (Table 2 ) [ 40 45 ], of which I am men’s health [ 40 ] is the only study where PrEP adherence formed the outcome measure. In this study, an overall compliance rate of 73 % among young black MSM was found.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the prominence of internet, mobile and application communication within young MSM communities with regard to gay in-group socialising, and sexual partner seeking [ 54 ]. Finally, we identified one study [ 40 ] that discussed adherence to pre-exposure prophylaxis (PrEP) in young MSM of colour. This is important in view of the promising findings from recent clinical trials that PrEP constitutes an effective barrier against HIV infection among MSM [ 55 ].…”
Section: Discussionmentioning
confidence: 99%